2000
DOI: 10.1007/pl00013909
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Low pH on the Induction of Root Hair Formation in Young Lettuce (Lactuca sativa L. cv. Grand Rapids) Seedlings

Abstract: When young lettuce seedlings were cultured hydroponically under acidic conditions and continuous white light, elongation growth of the primary root was inhibited depending on the lowering of pH in the range 5.5 to 3.5.On the other hand, fresh weights of shoots and roots were scarcely influenced in the pH range from 5.5 to 4.0.Vigorous root hair formation was observed in the seedlings cultured under low pH condition. The amount of root hairs formed in the pH range from 4.0 to 4.5 was about seven times greater t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
9
1

Relationship

5
5

Authors

Journals

citations
Cited by 32 publications
(10 citation statements)
references
References 28 publications
1
9
0
Order By: Relevance
“…Based on this report, we suggest that the decrease in Mn uptake at low pH is caused not by decreased Mn availability in the medium, but by a decrease in Mn uptake by lettuce roots. Inoue et al (2000) reported that root elongation was suppressed at low pH but this condition had little effect on the fresh weight of the shoot. Therefore, we considered the possibility that shoot growth could be suppressed by the excess Mn at pH 4, because of the suppression of root hair induction at low pH.…”
Section: Discussionmentioning
confidence: 96%
“…Based on this report, we suggest that the decrease in Mn uptake at low pH is caused not by decreased Mn availability in the medium, but by a decrease in Mn uptake by lettuce roots. Inoue et al (2000) reported that root elongation was suppressed at low pH but this condition had little effect on the fresh weight of the shoot. Therefore, we considered the possibility that shoot growth could be suppressed by the excess Mn at pH 4, because of the suppression of root hair induction at low pH.…”
Section: Discussionmentioning
confidence: 96%
“…It is a well-known phenomenon that acidification enhances activity of expansins (McQueenMason et al, 1992). Decreasing pH to a value of 4.0 to 4.5 strongly stimulated growth of root hairs in Lactuca sativa (Inoue et al, 2000). Accumulation of expansins in the cell wall domain in place of subsequent root hair outgrowth can promote local disassembling of cell wall components.…”
Section: Discussion the Role Of Expansins In Root Hair Developmentmentioning
confidence: 99%
“…Bethke et al 23 demonstrated the existence of apoplastic synthesis of NO from nitrite that requires low pH. Inoue et al 24 demonstrated that low pH induces RHF in young lettuce seedlings. Interestingly, it was clearly demonstrated that low pH (~4.5) at cell wall bulging of trichoblasts is required at the initiation phase of RHF.…”
Section: Discussionmentioning
confidence: 99%